#### Answer

x - 5

#### Work Step by Step

($x^{2}$ - 25) / (5 + x)
= (x + 5) (x - 5) / (x + 5)
= 1 * (x - 5)
= x - 5

Published by
Pearson

ISBN 10:
0321785045

ISBN 13:
978-0-32178-504-6

x - 5

($x^{2}$ - 25) / (5 + x)
= (x + 5) (x - 5) / (x + 5)
= 1 * (x - 5)
= x - 5

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.